GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, PROFESIONALISME GURU DAN PARTISIPASI KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMPN 2 LINGSAR - Habibi Yusran; Muhammad Makki; Abdul Kadir Jaelani; Heri Hadi Saputra; Mohamad Mustari (STKIP Pesisir Selatan, 2026)
Professional teachers are able to design creative learning, utilize information technology, and build a conducive learning climate. Teacher professionalism is closely linked to the success of the learning process and student academic achievement. This study aims to analyze the transformational leadership of the school principal, teacher professionalism, and community participation in supporting the improvement of educational quality at SMPN 2 Lingsar. The research employed a qualitative approach with a descriptive design to obtain an in-depth understanding of educational quality improvement practices. The research instruments included interview guidelines, observation sheets, and documentation as the main data sources. Data analysis was conducted through data reduction, data display, and systematic conclusion drawing. The findings indicate that transformational leadership, strong teacher professionalism, and active participation of the school committee and community significantly contribute to creating a conducive school climate and enhancing sustainable educational quality.